Faktor-Faktor Yang Berhubungan Dengan Tingkat Manfaat Bagi Penerima Beasiswa dan Peningkatan Kinerja SDM Unggul di Jambi Indonesia - Wilhelmus Hary Susilo (Jurnal Ekonomi dan Bisnis, 2014)
Organizer and better quality education strongly influenced by support funds. Hence, the government will provide support organizing of sustainable funding for education is good for all its citizens. This study is applied research aimed at giving them feedback implementer apply for the scholarship two models empirical short-term and long-term. Research methods used are quantitative data qualitative primary with the approach that can absorb aspirations from people. An examination used descriptive correlation-cross sectional. Results of testing the model A, Variable of information, requirements, mechanisms, level of adequacy, the use of cost has a positive and significant relationship with variable monitoring. Variables of information, requirements and the adequacy of monitoring, use and has a positive and significant relationship with variable benefits scholarships for the recipient. Variable selection mechanisms have a relationship that is negative and not significant to the variable benefit scholarships for the recipient. Research on Model B, which states that there is a significant relationship between variables; climate, financing, motivation, organization, job satisfaction and performance.